Characteristics and content of intrusive memories in PTSD and their changes with treatment. - Hackmann, A; Ehlers, A; Speckens, A; Clark, D (2004)
Although intrusive reexperiencing is a core symptom of postraumatic stress disorder (PTSD), relatively little is known about its phenomenology. The present study assessed the characteristics and content of intrusive trauma memories in 22 patients with PTSD, and followed their changes in the course of cognitive behavioral treatment. Patients had a small number of different intrusive memories (1-4, M = 2.2) that occurred in an invariable, repetitive way. The intrusions were distressing and had a vivid perceptual content. They appeared to the patient to be happening in the "here and now." With therapy, the frequency, vividness, distress, and nowness of the intrusions faded gradually. There was no exacerbation with imaginal reliving. The content of intrusions was classified by raters to test A. Ehlers et al.'s (2002) hypothesis that intrusive memories are usually of warning stimuli that signalled the moments with the greatest emotional impact. The results were consistent with this hypothesis.